Harnessing the Induction of CD8+ T-Cell Responses Through Metabolic Regulation by Pathogen-Recognition-Receptor Triggering in Antigen Presenting Cells - Nicoli, Francesco; Paul, Stéphane; Appay, Victor (Frontiers in Immunology, 2018)
Cytotoxic CD8+ T-cells are key players of the immune responses against viruses. During the priming of a CD8+ T-cell response, the activation of a naïve T-cell by a professional antigen presenting cell (APC) involves the induction of various intracellular and metabolic pathways. The modulation of these pathways at the level of APCs or T-cells offers great potential to enhance the induction of robust effector cells and the generation of long-lived memory cells. On the one hand, signaling through pathogen recognition receptors (PRRs) expressed by APCs can greatly influence T-cell priming, and the potential of several PRR ligands as adjuvants are being studied. On the other hand, the engagement of several metabolic processes, at play in APCs and T-cells upon stimulation, implies that modulating cellular metabolism can impact on priming efficacy. Here, we review recent efforts to understand the interplay between PRR mediated signaling and metabolic pathway modulation in this context, through three examples: interplay between TLR4 and fatty acid metabolism, between TLR9 and IDO, and between STING and autophagy. These initial works highlight the potential for harnessing the induction of antiviral CD8+ T-cell responses using synergistic modulation of metabolic and PRR pathways.